If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 = 11x Reorder the terms: 6 + 5x = 11x Solving 6 + 5x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 6 + 5x + -11x = 11x + -11x Combine like terms: 5x + -11x = -6x 6 + -6x = 11x + -11x Combine like terms: 11x + -11x = 0 6 + -6x = 0 Add '-6' to each side of the equation. 6 + -6 + -6x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -6x = 0 + -6 -6x = 0 + -6 Combine like terms: 0 + -6 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| -2+x=6x-17 | | 4[9-3(8m+1)]-8m= | | F(x)=9xln(3x)-9x | | 6+8x=5x+9 | | 4ln(x+2)+3ln(4x+9)= | | 4[2(x-3)]= | | 7y+y(6-8)= | | 3x+x=1.35 | | 40-n=4n+7 | | 3x+x=135 | | 7(x-1)=6x+1 | | X^2-13x+60=90 | | 88=2+2(8-5x) | | 8x+6=5x+5 | | g-4=-3 | | 22=x^2 | | (-x^5/2)^4 | | m-9=3 | | y=1.2+0.8(-2) | | ln(x)+ln(5x)=9 | | -89=x+75 | | 9y-5y(6-8)= | | 12+6(z+2)=5z+2 | | pt+51=76 | | 7y+y(2-8)= | | 6-4x^5=4-3x^2 | | (6+x)(x)=28 | | 6-4x*5=4-3x*2 | | h+9=-45 | | 6+x(x)=28 | | -16t^2-120t+500=700 | | -19n+16=-18n-5 |